2019
DOI: 10.1177/2158244019885125
|View full text |Cite
|
Sign up to set email alerts
|

How Do Sources of Self-Efficacy Predict Preservice Teachers’ Beliefs Related to Constructivist and Traditional Approaches to Teaching and Learning?

Abstract: Guided by Bandura’s theoretical construct of self-efficacy, in this study, we attempted to model the relationship between preservice elementary teachers’ sources of self-efficacy and their constructivist, and traditional beliefs related to teaching and learning by multiple linear regression analyses. Participants consist of 151 preservice elementary teachers at a state university. Results indicated that while mastery experience is significantly contributed to preservice elementary teachers’ constructivist teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 38 publications
2
20
0
2
Order By: Relevance
“…The study found that the practice of eliciting learners' ideas among the participants was deep-seated except for 4.7% who abandoned the practice, while the use of analogies and examples was largely adopted and honed within the classroom context. Thus, in the face of the complex realities of classroom contexts, instructional practices can be adopted and honed or abandoned depending on whether the pedagogical understanding is superficial or deep-seated, which has implications for their sense of self-efficacy (Bandura, 1995;Cansiz & Cansiz, 2019;Opfer & Pedder, 2011;Warner & Myers, 2008). Therefore, if teachers are helped to develop adequate pedagogical knowledge to appropriately integrate analogies and examples, they can elicit and expose learners' misconceptions, then address them (Duit et al, 2008;Lolita, 2015;Warner & Myers, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that the practice of eliciting learners' ideas among the participants was deep-seated except for 4.7% who abandoned the practice, while the use of analogies and examples was largely adopted and honed within the classroom context. Thus, in the face of the complex realities of classroom contexts, instructional practices can be adopted and honed or abandoned depending on whether the pedagogical understanding is superficial or deep-seated, which has implications for their sense of self-efficacy (Bandura, 1995;Cansiz & Cansiz, 2019;Opfer & Pedder, 2011;Warner & Myers, 2008). Therefore, if teachers are helped to develop adequate pedagogical knowledge to appropriately integrate analogies and examples, they can elicit and expose learners' misconceptions, then address them (Duit et al, 2008;Lolita, 2015;Warner & Myers, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the participants missing out on the consistent pedagogical supervision expertise of the HoS (Zeichner, 1996). The slight increase in average score indicates most participants did not develop a strong self-efficacy and, hence, found instructional practices challenging and difficult to implement (Bandura, 1997;Cansiz & Cansiz, 2019;Kazempour & Sadler, 2015).…”
Section: Effect Of Teaching Practice On Integration Of Interactive Instructional Practices In the Lecture Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method also defines the reasons for inefficiency in poorly performing departments and the changes that these departments must introduce to become more efficient. The method's usefulness as a planning tool is also discussed [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…SOS inventory has strong roots in the work ofBandura (2007). Inventory is the best predictor used to gauge teachers beliefs towards goal execution applied in the classrooms for students achievement scores(Cansiz & Cansiz, 2019;Henson, 1999). Part BRose and Medway (1981) Locus of Control Scale:To measure teachers classroom management beliefs, the researchers administered Rose and Medway (1981) locus of control scale.…”
mentioning
confidence: 99%